Aligned Growth of Hexagonal Boron Nitride Monolayer on Germanium. Issue 40 (26th August 2015) - Yin, Jun; Liu, Xiaofei; Lu, Wanglin; Li, Jidong; Cao, Yuanzhi; Li, Yao; Xu, Ying; Li, Xuemei; Zhou, Jun; Jin, Chuanhong; Guo, Wanlin
<x xml:space="preserve">Abstract</x> A hexagonal boron nitride monolayer with aligned orientations is grown on reusable semiconducting germanium. The number of primary orientations of the h‐BN domains depends on the symmetry of the underlying crystal face, and Ge (110) gives rise to only two opposite orientations. The structures and electrical properties of grain boundaries between h‐BN domains with opposite orientations are also systematically analyzed.